Air-breathing Mg-Cu/CuO fuel cell - R. Jayakrishnan; Aruna Raj; Akhil M. Anand; P C Harikrishnan; Athira Ayyappan (Journal of Engineering and Applied Science, 2024)
Abstract Magnesium fuel cells deliver higher electrical power output than lithium-ion batteries and have the potential to become an economically attractive alternative power source for domestic purposes. In place of noble metals in the air cathode of Mg fuel cells, we investigate the use of an integrated structure of a catalyst and current collector composed of a Cu/CuO hetero-structure. For a single cell, comprising of electrodes of dimension 3 cm × 1.5 cm with aqueous NaCl as the electrolyte, the Mg- Cu/CuO-based fuel cell shows an open-circuit voltage of 0.7 V and discharge current drain rate of 0.45 mA/s. A power density of 8.75 µWcm−2 is obtained with a CuO-based cathode when 1 M NaCl electrolyte is used. Relative to the magnesium-carbon-based fuel cell, the Mg-Cu/CuO fuel cell shows improved stability of the anode and cathode materials and extended operational time.